Hallux valgus associated to osteoarthritis: Clinical-radiological outcomes of modified SERI technique at mid- to long-term follow-up. A retrospective analysis. Issue 1 (January 2022) - Mosca, M.; Caravelli, S.; Vocale, E.; Fuiano, M.; Massimi, S.; Di Ponte, M.; Censoni, D.; Grassi, A.; Ceccarelli, F.; Zaffagnini, S.
Highlights: Treatment options for arthritic hallux valgus include joint-preserving surgical procedures, arthroplasties and arthrodesis of the first MTPJ. The aim of this study is to describe the mid to long-term follow-up results of this modified technique confirming the good outcomes. Modifications to the SERI technique could extend the indications of this procedure to those patients affected by hallux valgus with OA. Abstract: Introduction: Treatment of hallux valgus deformity associated with mild or moderate osteoarthritis (OA) is still a topic of debate. In the literature, there are few studies concerning the management of patients affected by this condition. This study aims to report the experience at mid- to long-term results of an original joint-preserving surgical technique. Materials and Methods: Patients affected by mild to moderate hallux valgus deformity and associated to grade 1–2 OA and treated with modified Simple-Effective-Rapid-Inexpensive (SERI) technique from 2008 to 2018 were selected. Inclusion criteria were mild or moderate hallux valgus angle (HVA) <40° and an intermetatarsal angle (IMA) <20° and associated grade 1–2 OA of the first metatarso-phalangeal joint (MTPJ). Results: 128 feet in 120 consecutive patients, undergone modified SERI procedure, have been retrospectively reviewed at a mean follow-up of 5.1 ± 3.8 years (range 2–11). American Orthopaedics Foot Ankle Society (AOFAS) score that was significantly improved from 44.2 ± 13.2 to 88.2 ± 9.6. Pre-operative average HVA and IMA values decreased respectively from 31.6° ± 3.9° to 9.1° ± 4.4° and from 16.2° ± 3.8° to 7.2° ± 3.1°. The average distal metatarsal articular angle (DMAA) value improved from 28.2° ± 6.5° to 7.1° ± 6°. OA of the first MTPJ highlighted a grade 1 in 46 feet and a grade 2 in 82 feet pre-operatively and a grade 0 in 30 feet, grade 1 in 82 feet, and grade 2 in 16 feet at the final follow-up. Conclusions: The modifications to the SERI technique could extend the indications to patients affected by hallux valgus with mild to moderate OA. The wider case series and the longer follow-up of this study make us believe this technique is very useful for improving the quality of life in these patients. Level of evidence: IV.